2016
DOI: 10.1002/ange.201605934
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten(VI) Carbyne/Bis(carbene) Tautomerization Enabled by N‐Donor SBA15 Surface Ligands: A Solid‐State NMR and DFT Study

Abstract: Designing supported well-defined bis(carbene) complexes remains akey challenge in heterogeneous catalysis. The reaction of W(CtBu)(CH 2 tBu) 3 with amine-modified mesoporous SBA15 silica, which has vicinal silanol/silylamine pairs [( SiOH)( SiNH 2 )],l eads to [( SiNH 2 À )( SiO À )W( CHtBu)(CH 2 tBu) 2 ]a nd [( SiNH 2 À )( SiO À )W( = CHtBu) 2 -(CH 2 tBu). Variable temperature, 1 H-1 H2 Dd ouble-quantum, 1 H-13 CH ETCOR, and HETCOR with spin diffusion solidstate NMR spectroscopydemonstrate tautomerization bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The W low loading in 4 (1.43 wt.%, Table S3, SI) does not allow clear observation of the quaternary carbon of W‐carbyne. This result was expected, since earlier work demonstrated that to measure the resonance of the carbyne in a species immobilized on oxide support it is necessary to have a high W loading (8 wt.%) and/or isotopically labeled W‐containing species …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The W low loading in 4 (1.43 wt.%, Table S3, SI) does not allow clear observation of the quaternary carbon of W‐carbyne. This result was expected, since earlier work demonstrated that to measure the resonance of the carbyne in a species immobilized on oxide support it is necessary to have a high W loading (8 wt.%) and/or isotopically labeled W‐containing species …”
Section: Resultssupporting
confidence: 76%
“…The 13 C SS NMR signals characteristic of the neopentyl ligands were observed at 34 and 102 ppm and assigned to CH 2 and CH 3 , respectively. Nonetheless, we observed a weak signal at 32 ppm that we assigned to the CH 3 group of the neopentylidyne fragment (Figure S13, SI) …”
Section: Resultsmentioning
confidence: 77%
“…Importantly, no clear indication of the formation of a Walkylidene complex, expected to display a signal at ∼10−11 ppm in the 1 NMR spectrum and in the 220−300 ppm region in the 13 C NMR spectrum, 16,84 was observed. Whereas tungsten forms stable metallacyclobutane intermediates, 74 tungsten alkylidene intermediates generated from supported tungsten alkyl complexes are generally difficult to observe, as a consequence of their high reactivity and lability.…”
Section: T H Imentioning
confidence: 96%
“…32 Previous computational studies of early-transition-metal alkylidyne complexes mainly focused on metathesis 28,45,46 and t a u t o m e r i z a t i o n b e t w e e n a l k y l i d y n e a n d b i s -(alkylidene). 31,[33][34][35][36]47,48 The grafting reaction of C-1 onto the γ-alumina surface has been studied by density functional theory (DFT) calculations. 17 The calculations showed that the grafting of C-1 occurs via direct electrophilic cleavage of the W−C bond by Al s OH to form the monografted surface complex [(SiO)W(C t Bu)(CH 2 t Bu) 3 ].…”
Section: ■ Introductionmentioning
confidence: 99%